THE EFFECT OF MANGROVE DENSITY TO ESTUARY WATER QUALITY BASED ON PHYSIC-CHEMIST PARAMETERS AT WONOREJO, SURABAYA - Putra, Beny Satrya Eka; Hendrasarie, Novirina (Directorate of Research and Community Service (DRPM), 2022)
Fishery in estuary make changes function of mangrove land and decreased, so that it affect water quality. This study aims to determine mangrove density and relation with the quality of wonorejo estuary waters. The method uses purposive random sampling and line plot method with a 10x10 meter plot to determine the criteria for mangrove density and water quality tests based on physic-chemical parameters and then correlated to test the effect. The results of the water quality analysis at the Wonorejo estuary with the optimum value at station 5 have an average parameter value of temperature (29°C), brightness (22 cm), current speed (0.083 m/s), TSS (55 mg/L), pH (7.36), salinity (5.5), DO (1.709 mg/L), COD (42.4 mg/L), nitrate (0.18 mg/L), and phosphate (1.045 mg/L). The criteria for mangrove density at each station include low density, medium density, and high dense density. Physic-chemical parameters related to mangrove density are temperature, brightness, salinity, and COD. Estuarine waters based on physic-chemical parameters, namely 40.3% salinity, 33.7% COD, 30.9% brightness, 30.8% temperature, 14% nitrate, 11.4% TSS, 8.1% current velocity, 1 .3% DO, and 0.1% phosphate affected by mangrove density.